FIRST LANGUAGE ACQUISITION ON A THREE-YEAR-OLD CHILD - Yuliana Friska; Moh. Thoyib Syafi'i (Acitya: Journal of Teaching and Education, 2021)
Studying children’s language acquisition is quite fascinating to be conducted because as we know that the astonishing advancement of their language obtaining from 0 to 3 years or more. The aim of the study is to obtain deep understanding about language acquisition on a three-year old child "Gadis Mardhiyah" and to observe language development of her. Besides, this study uses qualitative approach. In this case, researcher observes her daily conversation in her surrounding in order to get the natural result without any setting. This study was conducted at her house in Bintaro sector 9 Pd. Pucung Tangerang Selatan. Regarding this, the study was conducted for four weeks and preliminary study was done for a month before the researcher doing her observation. Data analysis was carried stage by stage in accordance prior to the focus of the problems. After the data obtained through observation and document inductively processed, then the next step is to define the meaning on the basis of phonological analysis, morphological analysis, syntactical analysis, and discourse analysis. Based on the analysis, it can be concluded that Gadis was able to communicate properly and appropriately according to her age.